Tinjauan Yuridis Pertanggungjawaban Pidana Pelaku Pengeroyokan yang Mengakibatkan Kematian dalam Putusan Nomor 442/Pid.B/2021/PN Jap - Ellsa Lisbert Kanan Rejauw; Abdul Malik Mufty; Nur Asmarani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Mob violence resulting in death is a criminal act that frequently occurs and raises legal issues concerning the criminal liability of perpetrators acting collectively. This study aims to analyze the criminal liability of perpetrators of mob violence resulting in death and to examine the judges’ legal considerations in Decision Number 442/Pid.B/2021/PN Jap. This research employs a normative juridical method using statutory and case approaches. Legal materials were collected through library research and analyzed qualitatively. The results show that the defendants fulfilled the elements of criminal liability, namely the capacity to be held responsible, the existence of intent, and the absence of justifying or excusing grounds. The court found the defendants legally and convincingly guilty of committing mob violence resulting in death as regulated under Article 170 paragraph (2) point 3 of the Indonesian Criminal Code. The judges’ considerations were based on witness testimonies, defendants’ statements, documentary evidence, and facts revealed during the trial. Nevertheless, the study finds that the sentencing imposed has not fully reflected the principle of individualization of punishment because the judgment did not specifically elaborate the degree of participation of each defendant. Therefore, greater attention should be given to the role and contribution of each perpetrator to ensure justice, legal certainty, and legal expediency.